HLA‐Associated Phenotypes in Youth with Autoimmune Diabetes. Issue 2 (23rd August 2012) - Black, Mary Helen; Lawrence, Jean M; Pihoker, Catherine; Dolan, Lawrence M; Anderson, Andrea; Rodriguez, Beatriz; Marcovina, Santica M.; Mayer‐Davis, Elizabeth J; Imperatore, Giuseppina; Dabelea, Dana
<x xml:space="preserve">Abstract</x> Objectives To examine human leukocyte antigen HLA DRB1–DQB1 haplotypes within a multi‐ethnic cohort and assess their association with characteristics of diabetes onset. Methods The sample included 1662 participants from the SEARCH for Diabetes in Youth Study who tested positive for GADA and/or IA‐2A autoantibodies. Blood drawn at the study visit was used to measure fasting C‐peptide (FCP) and genotype HLA DRB1 and DQB1 loci. Diabetic ketoacidosis (DKA) at diagnosis was determined from medical records. Multivariable linear and logistic regression models stratified by race/ethnicity were used to assess associations with DRB1–DQB1 haplotypes. Results The frequency of DRB1*03 susceptibility haplotypes ranged 27.5–28.9% in all racial/ethnic groups. The frequency of susceptibility DRB1*04–DQB1*0302 was higher in non‐Hispanic White (NHW; 34.1%) and Hispanic (38.9%) compared to non‐Hispanic Black (NHB; 20.8%) youth. Neutral and protective haplotypes were low frequency in all groups. DBR1*03 haplotypes were associated with younger age at diagnosis in NHW and positivity for multiple autoantibodies in Hispanics. DRB1*04–DQB1*0302 haplotypes were associated with multiple autoantibody positivity in NHW and Hispanics, and lower FCP and higher odds of DKA in Hispanics only. Although protective DRB1*04–DQB1*0301 haplotypes were associated with older age at diagnosis in NHW, they were also associated with multiple autoantibody positivity in these youth. Protective DRB1*13 haplotypes were associated with decreased odds of multiple autoantibody positivity in NHB youth. Conclusions The distribution of DRB1–DQB1 haplotypes and their association with onset‐related characteristics of autoimmune diabetes varies across major racial/ethnic groups in the USA. This may contribute to variation in clinical presentation of autoimmune diabetes by race/ethnicity.